(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2018)
Every consumer whether male or female when purchases a product or when in the decision making phase for purchasing a product passes through some process of mental decision comprising of the choice sets to reach at the correct decision. As a general practice, apart from the information gathering about the product, the decision making i.e. mental process are influenced by psychological variables also. This paper aims at finding whether the psychological factor ’Perceived Time Pressure’ differing across genders. The difference of psychological factor perceived time pressure among the male and female young consumers of Odisha are examined in this study and it has been observed that ’Perceived Time Pressure’ psychological factor differs between male and female consumer. This study of psychological aspect ’Perceived Time Pressure’ across genders will help in understanding the consumer decision making and behaviour of male and female consumers.